2010
DOI: 10.1080/02786820903426226
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Numerical Study on Deposition of Bioaerosols in a Scaled Chamber

Abstract: This work presents an experimental facility designed and built with the objective of understanding the deposition of bioaerosols in indoor environments. Multiple depositions of two microorganisms Staphylococcus and Micrococcus inside a test chamber were investigated under two air mixing conditions. Airflow rate was demonstrated to have an influence on the concentration homogeneity. An increased proportion of particle deposition was found in the floor section near the chamber wall opposite to the air inlet when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 29 publications
0
25
1
Order By: Relevance
“…Ideally all Reynolds' stresses are calculated individually as in the case of the RSM model. Although Wong et al [18] found good comparison using the RNG k-ε model, other studies have found that improvement achieved over standard k-ε models, still show significant differences compared to empirically measured DNS data [36].…”
Section: Cfd Methodologymentioning
confidence: 97%
See 2 more Smart Citations
“…Ideally all Reynolds' stresses are calculated individually as in the case of the RSM model. Although Wong et al [18] found good comparison using the RNG k-ε model, other studies have found that improvement achieved over standard k-ε models, still show significant differences compared to empirically measured DNS data [36].…”
Section: Cfd Methodologymentioning
confidence: 97%
“…With shedding of~10 6 skin flakes per day, they are consequently abundant in many health-care settings [17,18]. Staphylococcus aureus was chosen as the bacteriological agent given its ability to grow on general purpose media with ease.…”
Section: Bioaerosol Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Escherichia coli is regarded as highly susceptible to UVGI and are commonly used bioaerosols in UVGI system design [14,17,40]. Stock solutions of E. coli and S. marcescens were inoculated into nutrient agar plates (Oxoid), and the plates were incubated at 308C for 24 h. The incubation and harvesting methods were as described by Lai et al [17] and Wong et al [41]. The harvested cells were then transferred to 50 ml sterilized distilled water in a 24-jet collision nebulizer (BGI) for aerosolization.…”
Section: Generation and Collection Of Airborne Bacteriamentioning
confidence: 99%
“…Sub-micron sized particles are thought to remain airborne for prolonged periods of time [22], while larger droplets (>5 µm) are influenced by ventilation patterns, whereby the evaporation process followed by deposition may occur many meters from the initial source [23]. The environmental layout of a hospital room has been shown to have an impact on infection transmission, but biological experiments are only possible in specialist chambers [24,25]; in-vivo experimentation to discover where bioaerosols land in patient rooms is impossible using biological organisms [26]. Therefore, a non-biological surrogate that can faithfully mimic the trajectory of microorganisms in the indoor air is required.…”
Section: Introductionmentioning
confidence: 99%